Comparisons of Spatiotemporal and Ground Reaction Force Components of Gait Between Individuals with Congenital Vision Loss and Sighted Individuals. (July 2020) - Majlesi, Mahdi; Farahpour, Nader; Robertson, Gordon E.
Introduction: The understanding of abnormalities in biomechanical parameters of gait in individuals with vision loss (i.e., blindness or low vision) has clinical importance. The aims of this study were to compare the spatiotemporal and ground reaction force variables of sighted individuals with those with vision loss. Methods: Ten sighted males and 10 young males with congenital vision loss were recruited. A Vicon motion analysis system with four cameras and two Kistler force plates was used to quantify spatiotemporal and ground reaction force components of both groups during walking without shoes. Sighted individuals walked in eyes-open and eyes-closed conditions. Results: Results showed that the stride and step length, walking speed, the vertical and posterior–anterior reaction forces in heel contact and push-off phase, and the impulse of the control group during walking with the open- and closed-eyes conditions were significantly smaller than those in persons with vision loss ( p < .05). Discussion: Vision loss is associated with decreased step and stride length, slower walking, and smaller propulsive reaction force. These kinematic and kinetics alterations suggest an adaptation to a new neuromuscular response for dynamic postural control as a result of lack of vision. These alterations in the long term may result in rigidity and muscle weakness. Implications for practitioners: A rehabilitation program to enhance mobility and strength is suggested for individuals with vision loss.